Field reports form for submitting seasonal observations of Iowa birds, Jim Sinclair, spring 1992 - Sinclair, Jimet al (1992)
List of birds and locations contributed by Jim Sinclair. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1992. Plustek - flatbed